Modelling of thin layer drying of parsley leaves in a convective dryer and under open sun - Akpinar, EK; Bicer, Y; Cetinkaya, F (Elsevier Sci Ltd, 2006)
In this work, drying behaviour of parsley leaves was investigated in a convective dryer with forced convection at a fixed airflow rate of 1 m/s and drying air temperatures of 56, 67, 85 and 93 degrees C and under open sun with natural convection. The constant-rate period is absent from the drying curve. The drying process took place in the falling rate period. The drying data were fitted to the different mathematical models such as Newton, Page, Modified Page (I), Modified Page (II), Henderson and Pabis, Logarithmic, Two-term exponential, Verma et al. and Wang and Singh models. The performance of these models was investigated by comparing the determination of coefficient (R), reduced chi-square (chi (2)) and root mean square error (RMSE) between the observed and predicted moisture ratios. Among these models, the drying model developed by Page showed good agreement with the data obtained from the experiments of forced convection drying. The Verma et al. model has shown a better fit to the experimental parsley leaves data for open sun drying than the other models. The effect of drying air temperature on the constants and coefficients of Page model describing forced convection mode was investigated. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: drying; forced convection; open sun; mathematical modelling; natural convection; parsley leaves